ENHANCING STUDENTS’ READING COMPREHENSION IN DESCRIPTIVE TEXT THROUGH SUSTAINED SILENT READING - Bari, Fathul; Yuliana, Yohanes Gatot Sutapa; Sada, Clarry (English Language Education Study Program, 2021)
The researcher discovered that students did not understand reading descriptive text. Students did not know the meaning of the word. Sustained silent reading was a way to overcome students’ problem with reading. In this study, the researcher utilised classroom action research. The research was conducted in SMP Islam Walisongo Pontianak. The participants of the study were class 7 B with 36 students. For the first cycle based on the observation, implementing Sustained Silent Reading, the researcher watched students reading. The researcher discovered that some students did not earnestly read. Thereupon, the students did not understand reading descriptive text. Students did not know the meaning of the word. For the second cycle, there was something different at that time. The students started to understand what they were reading. The students began to pay attention to the teacher's elucidation about what they required to undertake on reading activity. They had started to enjoy reading descriptive text using sustained silent reading. The conclusion of this research was students could increase their understanding, reading in a descriptive text through sustained silent reading.